Perilaku dokter keluarga dan asma di Kota Manado - Sirait, Rolan Anderson; Ottay, Ronald Imanuel; Kuhon, Frelly Valentino (UNIVERSITAS SAM RATULANGI, 2023)
Background: Asthma is a heterogeneous disease typically characterized by chronic inflammation of the airways, manifested by respiratory symptoms such as wheezing, shortness of breath, and coughing. Data from Social Security Administrative Body for Health (BPJS Kesehatan) in 2019 showed significance increase in this province reached 1974 cases. Lifestyle in big cities like Manado City can increase the risk factors for asthma. The management of asthma requires a holistic approach, starting at the Primary Health Care Facilities (FKTP—Fasilitas Kesehatan Tingkat Pertama), such as community health centres and private practices doctors. However, studies have found that family physicians’ behaviour have limited knowledge concerning their knowledge, attitudes, and practices in asthma management.Aim: To assess the overview of behaviour (knowledge, attitudes, and practice) of family physicians regarding management of asthma in Manado City. Methods: This study was a descriptive study with a cross-sectional research design.Results: The level of knowledge was in the good category for 82% of family doctors in Manado City and in the sufficient category for 18% of family doctors. Attitude was categorized as good for 39% of family doctors and fair for 61% of them. The proportion of family doctors who had actions in the good category was 75%, 23% in the fair category, and 2% in the poor category.Conclusion: The behaviour of family doctors in the aspect of asthma knowledge was considered good, attitudes were at a sufficient level, and actions were concluded to be good.Keywords:behaviour; family physicians; asthma